Gastrointestinal colonisation and systemic spread of Candida albicans in mice treated with antibiotics and prednisolone. (April 2018) - Kobayashi-Sakamoto, Michiyo; Tamai, Riyoko; Isogai, Emiko; Kiyoura, Yusuke
Abstract: Normally, Candida albicans is a commensal microbe that resides in the human oral cavity, gut and vagina. However, the fungus can cause mucosal and systemic infections in immunocompromised individuals. The mechanism by which local mucosal infections progress to systemic candidiasis is poorly understood. Here, a murine model of gastrointestinal (GI) candidiasis was developed by inoculation of the oral cavity, followed by treatment with tetracycline (TC) and prednisolone (PSL). Temporal progression from a local infection of the oral cavity to a systemic infection was then monitored. Histological analysis of tissues from mice treated with both TC and PSL revealed massive infiltration of the tongue and stomach by hyphae. PSL increased the fungal burden in the tongue, stomach and small intestine, and facilitated dissemination to the spleen, kidney and liver within 3 days post-infection. Treatment with both TC and PSL supressed interferon (IFN)-γ and interleukin (IL)-17 (cytokines that play key roles in host defence against fungal infection) levels in the tongue, which were induced by C. albicans infection. In addition, the mucosal layer of the small intestine of mice treated with both TC and PSL was almost destroyed by the fungal infection; this may be a critical event that allows passage of the fungus across the mucosa and into the systemic circulation. Thus, this mouse model is useful for studying mechanisms underlying progression of C. albicans from a local infection of the oral cavity to a systemic infection in immunocompromised individuals. Graphical abstract: Image 1 Highlights: A murine model of GI tract and disseminated candidiasis was established. Prednisolone (PSL) increased murine susceptibility to colonisation by C. albicans. PSL increased the fungal burden, although the effect was organ-dependent. PSL decreased IL-17 and IFN-γ responses, although the effect was organ-dependent. PSL facilitated progression of oral infection to systemic candidiasis with gut damage.